PsycEXTRA Dataset 2014
DOI: 10.1037/e578192014-452
|View full text |Cite
|
Sign up to set email alerts
|

Self-talk as a regulatory mechanism: How you do it matters

Abstract: Does the language people use to refer to the self during introspection influence how they think, feel, and behave under social stress? If so, do these effects extend to socially anxious people who are particularly vulnerable to such stress? Seven studies explored these questions (total N ϭ 585). Studies 1a and 1b were proof-of-principle studies. They demonstrated that using non-first-person pronouns and one's own name (rather than first-person pronouns) during introspection enhances self-distancing. Studies 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A total of 20 studies (21 publications) reported the impact of mobile apps on the severity of depressive symptoms among youth (Bruehlman-Senecal, 2020;Bruhns, 2021;Egilsson, 2021;Fish, 2019;Fitzpatrick, 2017;Flett, 2019;Hammonds, 2015;Hur, 2018;Kageyama, 2021;Kauer, 2012;Lee, 2018;Levin, 2020;Liu, 2022;McCloud, 2020;Ponzo, 2020;Reid, 2011;Sun, 2022;Teng, 2019;Thabrew, 2022;Torok, 2022;Visser, 2020).…”
Section: Mean Effect Of Mobile Apps On Depressive Symptomsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 20 studies (21 publications) reported the impact of mobile apps on the severity of depressive symptoms among youth (Bruehlman-Senecal, 2020;Bruhns, 2021;Egilsson, 2021;Fish, 2019;Fitzpatrick, 2017;Flett, 2019;Hammonds, 2015;Hur, 2018;Kageyama, 2021;Kauer, 2012;Lee, 2018;Levin, 2020;Liu, 2022;McCloud, 2020;Ponzo, 2020;Reid, 2011;Sun, 2022;Teng, 2019;Thabrew, 2022;Torok, 2022;Visser, 2020).…”
Section: Mean Effect Of Mobile Apps On Depressive Symptomsmentioning
confidence: 99%
“…Three additional studies compared the severity of anxiety symptoms among participants receiving mobile apps to those receiving withheld controls (Bruehlman-Senecal, 2020;Egilsson, 2021;Kageyama, 2021), but the clinical heterogeneity arising from the variability of mental health therapy designs prevented the pooling of results. The mobile apps used different techniques to manage anxiety symptoms, including cognitive bias modification or positive stimulation (Kageyama, 2021), gamified health promotion (Egilsson, 2021), or social skill building to address loneliness (Bruehlman-Senecal, 2020).…”
Section: Mean Effect Of Mobile Apps On Anxiety Symptomsmentioning
confidence: 99%
See 2 more Smart Citations